Erratic journey of CRISPR/Cas9 in oncology from bench-work to successful-clinical therapy. (2021) - Sarkar, Esha; Khan, Afreen
Highlights: Worldwide discovery and advancements in CRISPR technique, making it a popular tool in genome-editing. Gene editing using CRISPR/Cas9 is feasible, time and cost effective as compared to other gene-editing tools. Pre-clinical and clinical trials studies done on cancer using CRISPR shows promising results. First ever successful human clinical trial showed the safety of CRISPR in therapeutics and may be used as a tool for cancer treatment in future. Controversies and ethical concerns regarding the use of CRISPR in germ-line editing. Abstract: CRISPR is a customized molecular scissor, comprising genetic guide made of RNA and an enzyme, Cas9 which snips DNA in simpler, cheaper and more precise way than any other gene editing tools. In recent years CRISPR/Cas has taken the research world by storm being go-to genome editor for potential gene therapy to fix cancer as well as several hereditary disorders. This review explores the literature around the mechanism of Nobel winning CRISPR/Cas9 and its journey from its discovery to various pre-clinical and clinical trials in oncology, focusing mostly on PD-1 knockout CAR-T cell therapy. It also discusses the hurdles and ethical dispute associated with CRISPR, such as unintended on-target and off-target cuts, embryonic germ-line editing. Despite the controversies regarding the safety of this technique, many studies reported promising results on targeting cancer and other diseases using CRISPR/Cas9. Outcomes from the first successful clinical trial showed the beneficial long term effect on genetically modified T-cells in targeting cancer cells which opens the door for CRISPR to be the most preferred technique to help treating cancer and other diseases in future. As far as germ-line editing is concerned, further studies are needed to support the safety of this technique in humans fixing genetic disorders and mutations. Therefore till date only somatic cell editing is ethically approved.